Conductivity as a Sensor for Monitoring Relative Magnesium Corrosion Rates in Real‐time, in Serum‐containing Media under Cell Culture Conditions. Issue 12 (21st July 2016) - Ojo, Kolade; Hopkins, Tracy; Joshi, Madhura; Salunke, Pravahan; Zhang, Guangqi; Nahan, Keaton; Zhang, Zhannping; Zhao, Daoli; Pixley, Sarah K.; Shanov, Vesselin; Heineman, William R.
Abstract: Because controlling the corrosion rate of magnesium metal will be crucial to the success of biomedical implants containing pure magnesium or magnesium alloys, many ways have been sought to improve in vitro tests to analyze corrosion rates, and also to identify new methods of preparing or post‐processing magnesium. In this work, for an in vitro assay, we explored the use of a commercially available conductivity sensor to study magnesium corrosion under cell culture conditions that duplicate many physiologically appropriate parameters. With this sensor, we studied the corrosion of two previously untested magnesium single crystal samples that differed in surface treatments that could alter corrosion rates. The results show that the relative conductivity changes in (mS/cm) over the total time of immersion were proportional to the corrosion rates in (mm/y) and also to the total magnesium released, as detected by inductively coupled plasma mass spectrometry (ICP‐MS). Abstract :